LEKSIKON JAGUNG DALAM MASYARAKAT TUTUR JAWA - Fitri Febriyanti; Sulistyowati Sulistyowati (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract: The formation of corn’s lexicons in Javanese. This study aims to describe the constituent elements and the type of reference from corn’s lexicons in Javanese. The type of this study is qualitative descriptive by using semantics theory approach. Methods of data collection are literature study and interview. The source of data comes from informant who’s working as farmer in Sragen and Pemalang regency. The numbers of informants are three people in each regency. The data were analyzed by ‘teknik pilah’ followed by ‘teknik hubung banding’. The results shows (1) the forming element of attributes are word and phrase, and (2) the type of reference consists of three categories, i.e. functions of maize plants, morphology of maize plants, and cultivation of maize plants.